Performance of Quails Given Ration Containing Dragon Fruit Skin Fermented Neurospora crassa - Doharni Pane; Rahmaini Pakpahan (Jurnal Pertanian Tropik, 2019)
Quail is one type of poultry that must be developed because it has the potential to produce animalprotein needs for humans, namely meat and eggs. Because the meat and quail eggs are in greatdemand by the community, their maintenance is almost evenly distributed throughout Indonesia.Privileges of quails include fast production, do not require large capital, easy maintenance, and donot require large tracts of land. The aimed of this experiment was to determine the effect of providingdragon fruit skin-fermented (DFSF) with fungi Neurospora crassa as an alternative feed material tothe performance of quails. The research method are experiments using completely randomized design(CRD), with 5 treatments and 4 replications. if there is a real or very real difference that will be followedby Duncan's distance test. The treatments given are: A = without giving DFSF, B = giving 4% DFSF,C = giving 8% DFSF, D = giving 12% DFSF and E = giving 16% DFSF. The results showed thatdifferences in the level of DFSF in quail ration gave no significant effect on feed intake, body weightgain and feed conversion of quail ration. It can be concluded that the administration of DFSF up tothe level of 16% in the ration can be used as alternative feed ingredients without affecting feed intake,body weight gain and quail feed conversion.